ANALISIS KELAYAKAN FINANSIAL PEMBANGUNAN JALAN TOL BENOA-BANDARA-NUSA DUA - A.A Astri Dewi; P. Alit Suthanaya; D. M. Priyantha Wedagama (JURNAL SPEKTRAN, 2013)
By Pass Ngurah Rai is the only primary arterial road linking the traffic flow of people and goods from Ngurah Rai Airport to Nusa Dua. Peak hour traffic flow condition has exceeded the capacity of the road. To solve the above problems, it is planned to build toll roads Benoa-Bandara-Nusa Dua. The objectives of this study were to analyze the performance of existing roads with and without the toll road, the rates applicable to service users and to analyze the financial feasibility of the investment of the project.   Analysis was performed for several scenarios, including the scenario-1, assuming traffic growth factor of i = 9.96% / year, the interest rate 16% / year, inflation accounted for 8.506% / year and the toll rates using rates set by the Jasa Marga. All of the cost including land acquisition and construction costs were provided by investors. It was found that for the scenario-1, the  NPV is Rp 1,586,137,984,347, -, BCR: 0.4754 and IRR 3, 8676%. The results of the financial analysis indicated that investment of the toll roads Benoa-Bandara-Nusa Dua is not financially feasible. In order for this project to be financially feasible, the growth rate of vehicles should be at least i = 14.7% / year.